THE ROLE OF O. HENRY'S SHORT FICTION IN SHAPING AMERICAN LITERARY TRADITIONS - Karimova Feruza Zokirjon qizi (Modern American Journals, 2025)
William Sydney Porter, known by his pen name O. Henry, transformed the short story format through his skillful integration of irony, humor, and plot twists. Set predominantly in urban contexts, his narratives delve into universal themes such as love, personal sacrifice, and life’s inherent unpredictability. This article investigates O. Henry’s contribution to American literature, with an emphasis on his narrative structures, thematic focus, and enduring influence on later generations of writers. Through exemplary stories like "The Gift of the Magi" and "The Ransom of Red Chief", O. Henry played a pivotal role in elevating the short story into a respected literary genre, leaving behind a significant literary heritage that continues to inspire contemporary storytelling. His works exemplify the strength of compact narratives and the lasting effect of unexpected conclusions.
Keywords: O. Henry, American fiction, irony, narrative twist, literary heritage, urban setting, short story tradition, The Gift of the Magi, The Ransom of Red Chief, literary influence, emotional depth, storytelling techniques, moral insight.